A házasságkötések számának alakulása Mezőhegyesen - Zsótér, Brigitta (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
During the examined period the number of matrimonies drastically decreased. The reasons can be the following ones: firstly, the biggest firm of the settlement, which gave the highest number of workplaces, was closed down at the end of the 90s, then the majority of the young intelligentsia moved, together with their families, to the neighboring big cities, the children of these families are now at the marriageable age. The other reason: the young who went to the neighboring big cities (for example: to Szeged) in their teens to study there, came back to Mezőhegyes in a very small number because they did not find work there. The third possible reason: the financial support given by the local authority and by the biggest employer of the settlement - Mezőhegyesi Ménesbirtok Zrt. - to the young couple ceased to exist. The majority of the local marriages is between inhabitants of Mezőhegyes. There is a certain proportion where the wife or the husband is not from Mezőhegyes. In the case of some marriages both parts of the couple are not local inhabitants. The number of settlers and so the number of marriages can be increased with new workplaces, with supports from both the local authority and the employers.